Protected areas are not enough to protect blue carbon ecosystems and their services - Chmura, Gail L. (Frontiers in Marine Science, 2025)
Carbon credits generally cannot be awarded for organic carbon stored in salt marshes (called “blue carbon”) that are already protected. To be approved projects must provide activities that are in addition to this protection, more than what is occurring through “business-as-usual”. This requirement is referred to as “additionality”. “Protection” usually is considered to constitute prevention of direct disturbance to a marsh. However, threats to marshes often occur outside the borders of the protected area and amelioration of such threats should be eligible for blue carbon crediting. This paper reviews the threats of coastal squeeze, excessive nitrogen loading, deprivation of allochthonous sediments, and waterfowl grazing. Although the impacts can result in loss of marsh area and erosion of their carbon-rich soil, these threats are the result of activities in the watershed outside the bounds of the protected area. Some examples of actions within watersheds that reduce or remove these threats are provided and should be fundable through carbon credits.